Prevalence of Musculoskeletal Ailments and Associated Factors among Shoemakers in Kolkata, West Bengal - Swapnodeep Sarkar; Badal Kumar Sahu; Amitabha Chattopadhyay; Saikat Bhattacharya (Occupational Health and Safety Society of Nepal, 2024)
Introduction: Foot covering was one of the first things made by our primitive ancestors. Shoes have played an important role in human culture throughout history. Shoemakers and their health have attracted less attention than the shoes themselves. Musculo-skeletal problems were explored in this study to find out the prevalence and associated factors among the workers of the shoe making community in Kolkata, West Bengal. Methods: The study was done where shoemakers of the study area were considered and basic information on socio-economic status, demographic characteristics, pattern of musculo-skeletal morbidities. Community based cross-sectional study design was adopted and data collection was done through observation, interview and clinical examination. Results: This study found high prevalence (45.6%) of musculo-skeletal ailments among the shoe making workers and among all the ailments considered, most of them were suffering from 'pain in limb joints' (34.3%) followed by 'low back pain' (32.9%) and 'neck pain' (31.5%). Chi-square for linear trend analysis showed increasing odds ratio from 1 to 11.16 when the total duration of work for the shoemakers increased from less than 5 years to more than 21 years which was also statistically significant (χ2 = 21.82; p < 0.01). Similar trend was observed where odd ratio increased from 1 to 2.95 when daily working hours increased from less than 9 hours to more than 12 hours. (χ2 = 2.95; p < 0.09). Conclusion: Our study concluded high prevalence of musculo-skeletal ailments among shoe making workers and those are in increasing in linear trend analysis.